Osteogenesis imperfecta associated with dentinogenesis imperfecta (Research, Society and Development, 2022)
Objective: The present work aims to review the literature on the oral manifestations of Osteogenesis Imperfecta. Methodology: An integrative, qualitative, descriptive literature review using the SciELO databases - Scientific Electronic Library Online, PubMed- National Library of Medicine and the LILACS. Results: The selected studies evaluated patients with OI presenting its four types of variations, associated or not with other manifestations in the oral cavity, ID being one of the mentioned ones. The age was between 00 and 15 years, being considered children and adolescents. Discussion: OI is a hereditary pathology, whose main characteristic is bone fragility, with a high predisposition to fracture. DI affects the formation of collagen fibrins in dentin, which leads to morphological changes that affect dental structure and aesthetics. Conclusion: Osteogenesis imperfecta is a genetic pathology, with changes in the COL1A1 and COL1A2 phenotypes, which are responsible for the production of type 1 collagen, the disorder caused by changes in its production, affect patients in multiple ways, resulting in fractures from the childhood.